COVID-19 PANDEMIC: THE INFLUENCE OF FULL-ONLINE LEARNING FOR ELEMENTARY SCHOOL IN RURAL AREAS - Bramianto Setiawan; Vina Iasha (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2020)
AbstractThe Indonesian government launched an online learning program in the education area to break the chainof the coronavirus (covid-19) spreading. But, online learning requires more facilities such as internet access and smartphone/notebook which is not all equipped in rural areas. Therefore, this research has aimed to know the situation of the online learning process in rural areas during the co-19 pandemic. The research was conducted in Purwosari sub-district, Bojonegoro district, East Java with 53 of elementary school teachers as the participant. Online questionnaires that consist of 5 statements were used to collect the data. This research showed that the Whatsapp group was the famous platform for online learning. Besides that, the teachers have been facilitated by the school in online learning. On the other hand, internet access, learning innovation, and students’ facilities for online learning become obstacles in online learning in rural areas.Keywords:covid-19; learning process; elementary school; rural area